“El trabajo informal y su incidencia socio-económica en la economía familiar del cantón guayaquil, 2023” - Cuero Ortiz, José Luis (2024)
Informal work, without a contract or social security, affects more than 40% of the population in Guayaquil and negatively impacts household economics by reducing income and limiting personal development. The fundamental purpose of this research was to analyze informal work and its socio-economic impact on family economics in the canton of Guayaquil. The methodological process of the research was field-based, descriptive, and documentary. The techniques used were direct observation and the construction of an instrument directed at informal traders in the northern area of Guayaquil. Thanks to the construct, data could be tabulated and subsequently, the final results were extracted to fulfill the established objectives. Among the main findings, it was found that the socio-economic situation of informal workers in the northern zone of the canton of Guayaquil is mostly irregular, proving to be one of the most vulnerable sectors within the local economy due to the scarcity of opportunities and microcredit facilities, in addition to the almost non-existent social security and public safety. It is concluded that this economic activity generates incipient liquidity for the involved members, however, it allows them to energize their family economies, making it necessary to generate a proposal for public policies aimed at implementing training workshops to strengthen the informal economy sector in the northern zone of the canton Guayaquil. It is important to highlight that in the bay and in the northern area comprised of: northern Florida, casuarina and the entrance to the flower paradise, most of the informal trade is concentrated, along with the formal trade, although this research work may not be true. It would seem that it should be carried out in everything in the Guayaquil canton, specifically in its entire geographical extension, it is no less true that due to the characteristic of the subject, commerce is concentrated in the places described above, so for the lifting of the sample we only focus on these places, because it offers the homogeneity of cases in the different types of activity in which people carry out informal work, technically speaking we say that for this case in particular there was a collection of information by clusters, these clusters being: the bay and the northern area comprised of: north Florida, casuarina and the entrance to flower paradise. It is also clear that the sample was chosen randomly once the number of surveys to be carried out was determined in accordance with the statistical sample formula with a confidence level of 90%, an error of 10% and a Z alpha of 1.645, being the population 470,000 informal workers in the Guayaquil canton.